Integrating Religious Moderation Values in MATSAMA: an Innovative Case Study at MIN 2 Sumenep - Nur Aini; Maimun Maimun; St Wikowati; Nur Gilang Ramadhan Al Haris; Maysurah Maysurah (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study examines the implementation of religious moderation education in the Masa Ta’aruf Siswa Madrasah (MATSAMA) activities at MIN 2 Sumenep, Madura, focusing on institutional policies, activity processes, stakeholder responses, and their implications. Using a qualitative case study approach, data were collected through observation, interviews, focus group discussions, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that MIN 2 Sumenep systematically integrates religious moderation into MATSAMA through collaboration with Dharma Wanita Persatuan of the Ministry of Religious Affairs, which has designated this program for all madrasahs in Sumenep Regency. Five main policies were identified: formal integration, collaboration, a contextual pedagogical approach, curriculum integration, and evaluation mechanisms. The innovative CINTA BERUTANG approach (Storytelling, Narration, Question and Answer, Singing, and Playing Snakes and Ladders), using a 12-square Snakes and Ladders game representing nine values of religious moderation, effectively facilitates learning for first-grade students aged 6-7 years. Responses from students, teachers, and the Dharma Wanita Persatuan of the Ministry of Religious Affairs indicate successful implementation, with impacts including increased affective, cognitive, and conative understanding. And provides practical implications for other madrasahs in designing innovative MATSAMA activities.